The effect of the rupiah exchange rate and return on assets on the stock prices of manufacturing companies listed in the LQ45 index during the 2020–2024 period - Zahra Khoirunis’ Apriliani; Suhono Suhono; Irvan Yoga Pardistya; Liya Megawati (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of the rupiah exchange rate and Return on Assets (ROA) on the stock prices of manufacturing companies included in the LQ45 index on the Indonesia Stock Exchange during the 2020–2024 period. In an increasingly volatile macroeconomic environment, understanding the determinants of stock price movements is essential for investors and corporate decision-making. Employing a quantitative research design, the study utilizes secondary data obtained from company financial statements, Bank Indonesia, and the Indonesia Stock Exchange. Data analysis was conducted using multiple linear regression to assess both partial and simultaneous effects of the independent variables on stock prices. The findings reveal that the rupiah exchange rate does not have a significant partial effect on stock prices, indicating that short-term currency fluctuations may not directly drive investor valuation in the observed firms. In contrast, ROA shows a significant but negative effect on stock prices, suggesting that higher accounting returns do not necessarily translate into higher market valuations within the sampled period. However, when examined jointly, both macroeconomic and firm-level financial variables significantly influence stock prices, explaining approximately 18.6% of their variation. These results highlight that stock price movements are shaped by a combination of internal financial performance and external macroeconomic conditions, as well as broader market sentiment factors. The study emphasizes the importance of maintaining macroeconomic stability alongside sound corporate financial management to support stock performance in the manufacturing sector. It also suggests that future research should incorporate additional internal and external determinants to provide a more comprehensive explanation of stock price dynamics in emerging capital markets. Keywords: LQ45; Return on Assets; Rupiah Exchange Rate; Stock Price